The Relationship Between Perfectionism and Non-Suicidal Self Injury Incidents Among Nursing Students - Wulandari, Maharani Suci; Budury, Syiddatul; Soleha, Umdatus; Sharoni, Siti Khuzaimah Ahmad (Universitas Airlangga, 2025)
Students with perfectionistm personalities tend to always want to look perfect, so they are at high risk of experiencing despair, shame, anger, and depression. This condition often triggers Non-Suicidal Self Injury (NSSI) behavior as a way to vent or suppress emotions, which can cause body damage and the risk of infection. This study aims to analyze the Relationship between Perfectionist Personality and NSSI Incidents in Nursing Undergraduate Students. This study uses a cross-sectional approach. The population of this study were 160 undergraduate nursing students at Semester 7. The sample obtained 115 respondents using proportionate stratified. Data collection used the Hewitt and Flett Multidimensional Perfectionism Scale and the Inventory of Statements About Self Injury. Data analysis used the Spearman test with a significance level of α = 0.01. The results of the study were obtained from 115 respondents, almost half of which 40 (34.8%) respondents had a very high perfectionism personality, and almost half of which 55 (47.8%) respondents had very low Non-Suicidal Self Injury behavior. Based on the results of the Spearman test, the value of ρ = 0.000 was obtained, which means that there is a relationship between Perfectionism Personality and Non-Suicidal Self Injury Incidents among nursing students. The high level of perfectionism in nursing students, accompanied by low levels of NSSI, indicates that most of them have adaptive behavioral patterns. This means that even though they tend to be perfectionists, they are able to manage stress without engaging in destructive behavior. It is expected that the University will strengthen the counseling or campus psychologist services by holding regular counseling sessions that are scheduled regularly. This can help students cope with stress, anxiety, and other mental health issues, including preventing perfectionism personality and NSSI behavior.